1998
DOI: 10.1001/archinte.158.7.761
|View full text |Cite
|
Sign up to set email alerts
|

Carotid and Lower Extremity Arterial Disease in Patients With Renal Artery Atherosclerosis

Abstract: There was a strong association between severe renal artery atherosclerosis and severe carotid artery disease. Patients with renal artery disease also had a high prevalence of lower extremity arterial disease. In this patient population, screening for lower extremity arterial disease can be reserved for those with signs or symptoms of peripheral ischemia. Noninvasive carotid screening is justified in patients with renal artery disease to detect asymptomatic lesions that require either immediate surgical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 38 publications
2
21
0
2
Order By: Relevance
“…21 An overall trend for patients with increasingly severe renal artery disease to have increasingly severe degrees of carotid disease has also been reported. 22 The prevalence of severe renal artery stenosis among stroke patients with carotid arterial disease is as yet undefined.…”
Section: Discussionmentioning
confidence: 99%
“…21 An overall trend for patients with increasingly severe renal artery disease to have increasingly severe degrees of carotid disease has also been reported. 22 The prevalence of severe renal artery stenosis among stroke patients with carotid arterial disease is as yet undefined.…”
Section: Discussionmentioning
confidence: 99%
“…(i.e., greater than 50%) have been reported in 11% to 18% of patients (621)(622)(623). Prevalence studies have also demonstrated significant RAS in 22% to 59% of patients with PAD (616)(617)(618)(619)(624)(625)(626)(627)(628)(629)(630). In one necropsy study, RAS greater than 50% was found in 53% of 295 unselected, consecutive examinations (631).…”
Section: Prevalence and Natural Historymentioning
confidence: 99%
“…Given the high prevalence of RAS in individuals with coronary artery disease (621,718,719) and peripheral vascular disease (619,(624)(625)(626)(627)(628)(629)(630) that warrant catheter angiography, the use of screening flush aortography (not selective renal angiography) at the time of coronary and peripheral vascular angiography has been proposed. Such studies may be appropriate (by operators skilled in the performance and evaluation of RAS using flush aortography) when individuals who will be undergoing coronary or limb angiography have clinical indicators for significant renal arterial occlusive disease.…”
Section: Magnetic Resonance Angiographymentioning
confidence: 99%
“…Zierler et al [12]found that among such patients, 19% had severe carotid disease and 21% had severe peripheral vascular disease. In a similar study among patients with renovascular disease, 26% had moderate and 18% severe carotid stenosis [13].…”
Section: Introductionmentioning
confidence: 99%